2018
DOI: 10.20961/carakatani.v32i1.15928
|View full text |Cite
|
Sign up to set email alerts
|

Efisiensi Produksi Sapi Potong Pada Peternakan Rakyat Pada Musim Kemarau Di Daerah Pertanian Lahan Kering Kabupaten Gunungkidul

Abstract: <p><em>This research was conducted to know the production efficiency of beef cattle in smallholder farmer in a dry farming area at dry season. Research has been started on June and finished on September (dry season) at smallholder farmer in the village Kemejing, Semin subdistrict, district Gunungkidul, DIY. The research materials are 28 heads of beef cattle from 17 farmers, which consist of 10 heads of PO breed, 10 heads of a Simpo breed, and 8 heads of Limpo breed with 292.25 kg of initial body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
1
1
1
6
Order By: Relevance
“…The % DM intake in the dryland agricultural areas of Gunungkidul Regency was ranging from 1.91 to. 5.19% with an average was 2.74% [14]. The results of this study were similar to those reported by Paramita et al [15] in 1.5 years old PO cattle, weighing 180-200 kg, the DM intake was 2.52-2.74%.…”
Section: Feed Intake Feed Efficiency and Feed Conversion Ratiosupporting
confidence: 91%
“…The % DM intake in the dryland agricultural areas of Gunungkidul Regency was ranging from 1.91 to. 5.19% with an average was 2.74% [14]. The results of this study were similar to those reported by Paramita et al [15] in 1.5 years old PO cattle, weighing 180-200 kg, the DM intake was 2.52-2.74%.…”
Section: Feed Intake Feed Efficiency and Feed Conversion Ratiosupporting
confidence: 91%
“…Feed cost per gain (fc/g) adalah besarnya biaya pakan yang diperlukan ternak untuk menghasilkan 1 kg gain (Handayanta, et al, 2017) Feed cost per gain ini dihitung berdasarkan pada harga pakan yang dikeluarkan setiap hari oleh UPT PT dan HMT Jember dibagi dengan rerata pertambahan bobot badan yang dihasilkan.…”
Section: Estimasi Biaya Pakanunclassified
“…Kajian integrasi tanaman-ternak pada level komunitas maupun kawasan di Indonesia, sudah banyak dilaporkan (Kariyasa, 2005;Diwyanto et al, 2007;Siswati dan Nizar, 2012;Handayanta et al, 2017;Sandi et al, 2018). Petani tertarik menerapkan sistem tersebut karena dapat mencegah erosi, mengurangi ketergantungan pupuk, dan meningkatkan manfaat lahan, produksi tanaman, populasi ternak, ketahanan pangan serta pendapatan (Mugnisjah et al, 2000;Kariyasa, 2005;Diwyanto et al, 2007;Salendu dan Elly, 2012;Yuliani, 2014;Carof dan Godinot, 2018;Harahap et al, 2019).…”
Section: Abstrakunclassified
“…Persoalannya, sebagian ternak rakyat sering mengalami kekurangan pakan khususnya pada musim kemarau (Handayanta et al, 2017;Sandi et al, 2018) seperti pada Sekolah Peternakan Rakyat (SPR), sehingga keberlanjutan sistem menjadi terganggu. SPR adalah salah satu bentuk aksi komunitas yang bertujuan mendukung swasembada daging sapi (LPPM-IPB, 2015;Nuhung, 2015).…”
Section: Abstrakunclassified
See 1 more Smart Citation